Accuracy, inter-unit reliability and comparison between GPS and UWB-based tracking systems for measuring centripetal force during curvilinear locomotion - Granero-Gil, P.; Bastida-Castillo, A.; Rojas-Valverde, D.; Gómez-Carmona, C. D.; De La Cruz Sánchez, E.; Pino-Ortega, J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2021)
Curvilinear locomotion is important for team sports performance and requires data collection and monitoring of centripetal forces. Currently, the centripetal force can be measured by different sensors that compose inertial devices, but its accuracy needs to be assessed. Therefore, this research aimed to analyze the accuracy and inter-unit reliability of both global positioning (GPS)-based and ultra-wideband (UWB)-based systems for practical application in the field. Following institutional ethical approval and familiarization, 10 elite-level male soccer players performed six circuits on four tracks (6-m radius circle, 9.15-m radius circle, 12-m radius circle, and combined track locomotion) in both directions (three counter-clockwise and three clockwise) and were monitored by two tracking systems (GPS and UWB). The direct measurement was compared with the theoretical centripetal force calculated by photocells and spatial references. The UWB technology showed better accuracy (clockwise, bias =-1.34 N; counter-clockwise, bias = 1.09 N) than the GPS (clockwise, bias = -2.19 N; counter-clockwise, bias = 1.75 N) in centripetal force measurements. However, both tracking technologies obtained very large to nearly perfect reliability results (GPS: ICC = 0.76-0.96; UWB: ICC = 0.76-0.98). In conclusion, even though both technologies proved to be reliable and data could be compared between units, the UWB-based system demonstrated better accuracy than the GPS-based system to detect centripetal force during curvilinear locomotion.